Coincidence versus consequence: opportunities in multi-morbidity research and inflammation as a pervasive feature. Issue 3 (4th May 2017) - Gibson, David S.; Drain, Stephen; Kelly, Catriona; McGilligan, Victoria; McClean, Paula; Atkinson, Sarah D.; Murray, Elaine; McDowell, Andrew; Conway, Caroline; Watterson, Steven; Bjourson, Anthony J.
ABSTRACT: Introduction : Management of co- and multi-morbidity continues to represent a major clinical challenge. There remains a lack of understanding of how multiple pathologies or conditions co-evolve or interact and importantly how treatments should be combined to effectively improve outcomes. This review highlights the challenges presented to the clinical community in managing co- and multi-morbidity. Areas covered : The review focuses on frequently co-existing chronic conditions characterised by prolonged inflammation; these conditions include chronic obstructive pulmonary disease, rheumatoid arthritis, cardiovascular disease and certain forms of cancer. Literature searches were performed to retrieve relevant articles, particularly those published in the last 10–15 years. Within the review, current management strategies and opportunities for improvements are discussed. Problems with current clinical trial designs are described and the need emphasized for novel treatments and diagnostics for exemplar co- and multi-morbidities. We provide an overview of how precision medicine approaches could offer opportunities to treat multiple inflammation-driven disorders in a more comprehensive fashion. Expert commentary : This section emphasizes the need for further research on individual gene-environment interactions, with the view that environmental risk factors could offer a viable route to prevention of multi-morbidities.